1998
DOI: 10.1080/03079459808419348
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus infections in pigeons: A review

Abstract: In the present article, a review is given on adenovirosis in pigeons. Aetiology, pathogenesis, clinical signs, lesions, diagnosis and control of two clinical types of pigeon adenovirus infections are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 10 publications
(25 reference statements)
2
31
0
Order By: Relevance
“…Such molecular techniques have proved to be effective and common for identification of new viruses in recent times; nevertheless, a definitive diagnosis of viral infection has relied upon virus isolation. Although the use of a homologous cell culture system was reported to be preferable (McFerran & Adair, 2003), avian adenoviruses have also been isolated successfully from different species of birds using chicken cells (McFerran et al, 1976;Gassmann et al, 1981;Bouquet et al, 1982;Hess et al, 1998;Vereecken et al, 1998). In the present study the suspicion of adenovirus infection was confirmed by electron microscopic examination.…”
Section: Discussionsupporting
confidence: 64%
“…Such molecular techniques have proved to be effective and common for identification of new viruses in recent times; nevertheless, a definitive diagnosis of viral infection has relied upon virus isolation. Although the use of a homologous cell culture system was reported to be preferable (McFerran & Adair, 2003), avian adenoviruses have also been isolated successfully from different species of birds using chicken cells (McFerran et al, 1976;Gassmann et al, 1981;Bouquet et al, 1982;Hess et al, 1998;Vereecken et al, 1998). In the present study the suspicion of adenovirus infection was confirmed by electron microscopic examination.…”
Section: Discussionsupporting
confidence: 64%
“…Initial attempts to isolate AdVs from pigeons have been made by using primary chicken cells, consequently almost every known FAdV type has been obtained (McFerran et al, 1976;Vereecken et al, 1998). The first distinct pigeon AdV strain was reported by Hess et al (1998).…”
mentioning
confidence: 99%
“…Evidences for the presence of AdV in pigeons were compiled by electron microscopy, histology and serology (de Herdt et al, 1995;Vereecken et al, 1998). De Herdt et al (1995 described two different disease manifestations that had been suspected to be caused by specific pigeon AdVs.…”
mentioning
confidence: 99%
“…The type 1 affects mainly young pigeons (Duchatel et al, 2000), while type 2 affects birds aged 10 days to 6 years (Vereecken et al, 1998). In both types, the usually observed symptoms are vomiting, watery acute diarrhea, weight loss, anorexia and depression, with polyuria only in type 2 (Duchatel et al).…”
Section: Introductionmentioning
confidence: 99%
“…In type 2 or inclusion bodies hepatitis, the death of pigeons it was reported in 24 to 40 hours after the symptoms and mortality rate of 30 to 100% (Hess 1988 a, b;Vereecken et al;Duchatel et al;Wang & Chang, 2000).…”
Section: Introductionmentioning
confidence: 99%